Cervical vagal nerve stimulation impairs glucose tolerance and suppresses insulin release in conscious rats. Issue 24 (19th December 2018) - Stauss, Harald M.; Stangl, Hubert; Clark, Karen C.; Kwitek, Anne E.; Lira, Vitor A.
Abstract: Previously, we reported that cervical vagal nerve stimulation (VNS) increases blood glucose levels and inhibits insulin secretion in anesthetized rats through afferent signaling. Since afferent signaling is also thought to mediate the therapeutic effects of VNS in patients with therapy‐refractory epilepsy and major depression, the question arises if patients treated with VNS develop impaired glucose tolerance. Thus, we hypothesized that cervical VNS impairs glucose tolerance in conscious rats. Rats ( n = 7) were instrumented with telemetric blood pressure sensors and right‐ or left‐sided cervical vagal nerve stimulators (3 V, 5 Hz, 1 msec pulse duration, 1 h on 1 h off). Glucose tolerance tests (GTTs, 1.5 g dextrose/kg BW, i.p.) were performed after overnight fasting with the stimulators on or off (sham stimulation) in randomized order separated by 3–4 days. Overnight VNS did not alter mean levels of blood pressure or heart rate, but increased fasted blood glucose levels (140 ± 13 mg/dL vs. 109 ± 8 mg/dL, P < 0.05). The area under the blood glucose concentration curves of the GTTs was larger during VNS than sham stimulation (3499 ± 211 mg/dL*h vs. 1810 ± 234 mg/dL*h, P < 0.05). One hour into the GTTs, the serum insulin concentrations had decreased during VNS (−0.57 ± 0.25 ng/mL, P < 0.05) and increased during sham stimulation (+0.71 ± 0.15 ng/mL, P < 0.05) compared to the fasted baseline levels. These results demonstrate that chronic cervical VNS elevates fasted blood glucose levels and impairs glucose tolerance likely through inhibition of glucose‐induced insulin release in conscious rats. It remains to be determined if patients treated with VNS are at greater risk of developing glucose intolerance and type 2 diabetes. Abstract : This research demonstrates that cervical vagal nerve stimulation (VNS) impairs glucose tolerance and raises fasted blood glucose levels in conscious rats, likely through afferent signaling to the central nervous system. If these results translate to patients treated with cervical VNS for conditions such as epilepsy or depression remains to be investigated.